(3GdJeKjd GdJLGQj L(B1s - (3GdjGS(B, (3CHh YjOs ((3HjQhJ(B:s (3efThQGJ GdMdHj GdMbhbjI(B,s, 2009)
(3GdCMcGe GdYGeI aj GdeDSSI GdJLGQjI(B- (3GdYbhO GdhGQOI Ydi GdeDSSI GdJLGQjI(B- (3Qgf GdeDSSI GdJLGQjI(B- (3YbO GdEOGQI GdMQI(B- (3bhGYO eNJdaI JWHb Ydi GdeDSSI GdJLGQjI(B.s
(3eQGLY U(B.371s
Keywords: (3GdHjYs; (3GdQgfs; (3GdYbhO GdJLGQjIs; (3GdeDSSI GdJLGQjIs